2013
DOI: 10.1556/avet.2012.058
|View full text |Cite
|
Sign up to set email alerts
|

Use of retinyl acetate, retinoic acid and insulin-like growth factor-I (IGF-I) to enhance goat embryo production

Abstract: Experiments were carried out to investigate the beneficial effects of retinyl acetate (RAc) and retinoic acid (RA) on goat oocyte maturation as well as the effects of insulin-like growth factor-I (IGF-I), RAc and RA during embryo culture under chemically defined conditions. In Experiment 1, in vitro maturation (IVM) was performed in a chemically defined basic maturation medium (bMM) supplemented with 0.3 μM RAc or 0.5 μM RA. Presumptive zygotes and embryos (2-4 cells) were cultured in droplets of potassium sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
3
14
0
2
Order By: Relevance
“…Duque et al (2002b) reported that addition of 9-cis-retinoic acid is beneficial to embryonic development in a quantitative and qualitative manner. Similar results were described by Lima et al (2006) in bovine and Chiamenti et al (2010) in caprine embryos, due to the fact that retinoids synchronise cellular events that trigger oocyte maturation, increase oocyte ability to be fertilised and potentiate further preimplantation embryonic development (Duque et al, 2002a;Lima et al, 2004;Lima et al, 2006;Chiamenti et al, 2010Chiamenti et al, , 2013. However, Cavalcanti did not observe any effect of retinyl acetate or 9-cis-retinoic acid on caprine oocyte nuclear and cytoplasmatic maturation.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Duque et al (2002b) reported that addition of 9-cis-retinoic acid is beneficial to embryonic development in a quantitative and qualitative manner. Similar results were described by Lima et al (2006) in bovine and Chiamenti et al (2010) in caprine embryos, due to the fact that retinoids synchronise cellular events that trigger oocyte maturation, increase oocyte ability to be fertilised and potentiate further preimplantation embryonic development (Duque et al, 2002a;Lima et al, 2004;Lima et al, 2006;Chiamenti et al, 2010Chiamenti et al, , 2013. However, Cavalcanti did not observe any effect of retinyl acetate or 9-cis-retinoic acid on caprine oocyte nuclear and cytoplasmatic maturation.…”
supporting
confidence: 80%
“…Retinoids, when supplemented during embryo culture, require co-culture systems, at least under some experimental conditions, in order to enhance embryonic development (Lima et al, 2004;Chiamenti et al, 2010Chiamenti et al, , 2013. This fact suggests that this paracrine signalling could be potentially useful for increasing embryonic development in vitro in other species and should be the focus of future research aimed at describing the molecular basis of retinoid embryotrophic properties in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoid compounds are found in the female reproductive tract and they were suggested to be able to improve the in vitro development of preimplantation embryos in several species (Duque et al , 2002a,b; Lima et al , 2004; Chiamenti et al , 2010, 2012). Retinoids are considered as a biological antioxidant network and an important regulators of redox signalling pathways (Ikeda et al , 2005; Alminana et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent protocols have used these compounds in the culture medium of embryos taking into account their deep effect upon cellular survival, proliferation, differentiation and embryonic morphogenesis (Noy, 2010; Rajesh et al , 2010; Rhinn & Dollé, 2012; Conceição et al , 2015; Conceição et al , 2016). It was found that the addition of retinoids to the culture medium enhances the subsequent preimplantation embryonic development in bovine embryos (Lima et al , 2004; Ahmed et al , 2016), and in goat embryos (Duque et al , 2002a,b; Lima et al , 2006; Chiamenti et al , 2010, 2012; Conceição et al , 2015). The positive effect of retinoids on embryo development could be induced directly by modulating growth factor gene expression or indirectly by improving the quality of mRNAs (Livingston et al , 2004).…”
Section: Introductionmentioning
confidence: 99%